Sleep Science and Practice - Kushida, Clete; Feng, Pingfu; Li, Shanqun; Dagan, Yaron; Nishino, Seiji; Zeitzer, Jamie; Han, Fang; Friedman, Leah; Inoue, Yuichi; Camacho, Macario; Grunstein, Ron; Philips, Craig; et al.
Sleep Science and Practice (SSP) is an open access journal for clinicians and researchers interested in the study of sleep and sleep medicine. The mission of this journal is to publish international basic and clinical sleep-related research that assists sleep specialists, scientists, and other professionals with their research and patient-care activities. The scope of the journal spans the following: Basic sleep concepts, science, deprivation, and mechanisms Translational sleep research Anatomy, physiology, and pharmacology of sleep Assessment, instrumentation, methodology, training, and policies of sleep Sleep disorders, such as insomnia, hypersomnias, circadian rhythm sleep disorders, sleep-related breathing disorders, sleep-related movement disorders, and parasomnias Sleep and comorbidities Sleep in special populations SSP welcomes manuscripts on  these topics and recognizes the interdisciplinary nature of sleep and sleep medicine through sleep-related research contributions from diverse fields such as neurology, immunology, pulmonary medicine, internal medicine, psychiatry, psychology, dentistry, pediatrics, endocrinology, genetics, and otolaryngology.